Pengaruh Customer Loyalty Terhadap Repurchase Intention Pasca Penurunan Ekonomi pada Produk Minuman Susu Bear Brand - Evi Rahmawati Agustina; Anak Agung Ketut Diatmika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The COVID-19 pandemic has led to a surge in demand for health products like Bear Brand. However, as the pandemic recedes, the company must adjust its strategy to preserve consumer loyalty in a competitive market. To encourage repeat purchases, Bear Brand should emphasize positive consumer experiences, build trust, and enhance motivation while upholding rigorous health standards and clear communication. This research seeks to examine the factors that affect consumers' decisions to repurchase Bear Brand milk drinks during the COVID-19 crisis. Conducted in the Jabodetabek region, the study employed a descriptive causal design with a quantitative method and used simple random sampling. Data was gathered from 150 individuals in Jabodetabek who had bought Bear Brand milk drinks at least twice in the past month, though the exact number of purchases was not specified. The data was analyzed using Structural Equation Modeling. The results indicate that customer motivation plays a significant role in increasing trust, loyalty, and repurchase intention for Bear Brand, with loyalty serving as a key link between trust and repurchase intention. To maintain and boost repeat purchases, Bear Brand should concentrate on highlighting health benefits, ensuring product quality, and fostering loyalty through effective programs.